Effect of sleep bruxism duration on perceived sleep quality in middle‐aged subjects - Neu, Daniel; Baniasadi, Nina; Newell, Johan; Styczen, David; Glineur, Régine; Mairesse, Olivier (European journal of oral sciences, 2018)
Sleep‐related bruxism may directly impact sleep quality. This study aims to evaluate potential relationships between sleep bruxism events and related daytime symptoms. We investigated 22 patients (42.1 ± 11.6 yr of age) with sleep bruxism in comparison with 12 good sleeper control subjects of similar age (41.0 ± 11.5 yr). Sleep bruxism was visually analyzed and categorized according to sleep stage, bruxism type (tonic/phasic) and duration. Clinical instruments comprised the Epworth Sleepiness, the Brugmann Fatigue Scale, and the Hospital Anxiety and Depression Rating Scale. Sleep quality was measured using the Pittsburgh Sleep Quality Index. Controls and patients with sleep bruxism presented similar sleep architecture. However, patients with sleep bruxism displayed significantly decreased sleep efficiency and higher sleep fragmentation. Perceived sleep quality was significantly worse in patients with sleep bruxism than in control subjects. Additionally, patients presented with significantly greater fatigue intensity and more affective symptoms than controls. The cumulative durations of sleep bruxism events (phasic, tonic, and combined) were significantly correlated with deterioration of sleep quality, whereas neither the event index per hour of sleep nor the count of event types (phasic/tonic) were related to sleep quality. Patients with sleep bruxism present with higher levels of daytime fatigue and sleepiness than control subjects who experience good sleep and may also exhibit impairments of sleep quality which are related to the duration of bruxism occurrence rather than to its frequency.